UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN SIRIH HUTAN (Piper aduncum L.) UNTUK MENGENDALIKAN PENYAKIT ANTRAKNOSA PADA BUAH CABAI MERAH PASCA PANEN - YETTI ELFINA ELFINA '; MUHAMMAD ALI '; LILIS ARYANTI ' (Universitas Riau, 2015)
ABSTRACTThis study aims to observe and obtain a better concentration of powder extract of wild betel leaf ability incontrolling anthracnose disease on red chili fruits.This study was performed experimentally using a completelyrandomized design consisting of 5 treatments and 4 replications thus obtained 20 trial units. The treatmentis the concentration of powder extract of wild betel leaf: KO= 0 g/l, K1= 25 g/l, K2= 50 g/l, K3= 75 g/l andK4= 100 g/l of water. The study consisted of two tests: in vitro inhibition of the fungus C. capsici and in vivoapplication of powder extract of wild betel leaf. The data were analyzed statistically using analysis ofvariance and the means were tested with Duncan ‘s New Multiple Range Test (DNMRT) at level 5%. Theresults showed that the concentration of powder extract of wild betel leaf significantly affected C. capsicigrowth and increase the percentage of fungal growth inhibition. Powder extract of wild betel leaf atconcentration of 100 g/ l of water quite capable the hold of anthracnose disease cause C. capsici, so as toreduce the intensity of attacks to 10% the effectiveness 52%.Key words: Red chili fruit, C. capsici, P. aduncum L.